Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.5194/angeo-22-3479-2004
|View full text |Cite
|
Sign up to set email alerts
|

<i>F</i>-region ionospheric perturbations in the low-latitude ionosphere during the geomagnetic storm of 25-27 August 1987

Abstract: Abstract.We have presented a comparison between the modeled N mF 2 and hmF 2, and N mF 2 and hmF 2 which were observed at the equatorial anomaly crest and close to the geomagnetic equator simultaneously by the Akita, Kokubunji, Yamagawa, Okinawa, Manila, Vanimo, and Darwin ionospheric sounders and by the middle and upper atmosphere (MU) radar (34.85 • N, 136.10 • E) during the 25-27 August 1987 geomagnetically storm-time period at low solar activity near 201 • , geomagnetic longitude. A comparison between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…Pavlov et al, 2004b), and, therefore, storm-time changes in these number densities in one of the crest regions or in both crest regions or in the trough region contribute to changes in the equatorial anomaly development. As far as the authors know, the relative role of these mechanisms in the equatorial anomaly suppression is studied only by Pavlov et al (2004b) for the 25-26 August 1987 geomagnetic storm. Pavlov et al (2004b) found that weak differences between disturbed and quiet E×B plasma drifts cannot be responsible for the suppression of the equatorial anomaly on 26 August, and this suppression is due to the action of storm-time changes in neutral winds and densities on the equatorial anomaly development. In this paper, we continue the study of the complex problem of the low-latitude ionospheric response to variations in the thermospheric wind, electric field, neutral composition, and neutral temperature during 17-22 March 1990 at solar maximum in the present case study, in which the electron density and temperature are measured simultaneously by the MU and Arecibo radars, and NmF2 and hmF2 are observed by the Kokubunji, Yamagawa, Okinawa, Manila, Vanimo, and Darwin ionospheric sounders.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Pavlov et al, 2004b), and, therefore, storm-time changes in these number densities in one of the crest regions or in both crest regions or in the trough region contribute to changes in the equatorial anomaly development. As far as the authors know, the relative role of these mechanisms in the equatorial anomaly suppression is studied only by Pavlov et al (2004b) for the 25-26 August 1987 geomagnetic storm. Pavlov et al (2004b) found that weak differences between disturbed and quiet E×B plasma drifts cannot be responsible for the suppression of the equatorial anomaly on 26 August, and this suppression is due to the action of storm-time changes in neutral winds and densities on the equatorial anomaly development. In this paper, we continue the study of the complex problem of the low-latitude ionospheric response to variations in the thermospheric wind, electric field, neutral composition, and neutral temperature during 17-22 March 1990 at solar maximum in the present case study, in which the electron density and temperature are measured simultaneously by the MU and Arecibo radars, and NmF2 and hmF2 are observed by the Kokubunji, Yamagawa, Okinawa, Manila, Vanimo, and Darwin ionospheric sounders.…”
mentioning
confidence: 99%
“…Pavlov et al (2004b) have presented a comparison of the modeled F2-layer peak densities, NmF2, and altitudes, hmF2, with NmF2 and hmF2, which were observed at low geomagnetic latitudes simultaneously by the Akita, Kokubunji, Yamagawa, Okinawa, Manila, Vanimo, and Darwin ionospheric sounders and by the MU radar during the 25-27 August 1987 geomagnetically storm, taking into account the storm-time changes in the thermospheric wind, the electric field, the neutral composition, and the neutral temperature. It is found by Pavlov et al (2004b) that the geomagnetic latitude variations in NmF2, calculated for 26 August 1987 (the recovery phase of the geomagnetic storm), differ significantly from those calculated for 25 August 1987 (before SSC and during the main phase of the geomagnetic storm) and for 27 August 1987 (after the geomagnetic storm). The Arecibo radar observations of the ionospheric F-region during the 1-5 May 1995 geomagnetic storm period have shown that there is the possibility of poleward expansion of the equatorial anomaly zone with the northern anomaly crest location close to the 29 • dip latitude (Buonsanto, 1999).…”
mentioning
confidence: 99%
See 3 more Smart Citations